(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
In the article the peculiarities of preposition semantics of the modern English language are viewed via the investigation of their syntagmatic properties in the scientific texts and in fiction. Detailed and complex analysis of the basic parameters characteristic of prepositions as well as their interrelations with nouns in two functional styles is performed here. Analyzing wide corpus of unadapted texts the most frequent combinations of prepositions with nouns were singled out and described applying quantitative calculations.